Valuing marine restoration beyond the 'too small and too expensive'. (November 2021) - McAfee, Dominic; Costanza, Robert; Connell, Sean D.
Abstract : Restoration is criticized as ineffectively small scale, a smoke screen against global-scale action. Yet, large-scale solutions arise from small-scale successes, which inject social values and optimism needed for global investment. Human values are central to achieving socio-ecological sustainability; understanding human behavior is now arguably more important than understanding the ecological processes.